Risk assessment of exposure to benzoic acid and benzene from consumption of functional drinks - Leesuraplanon C. (2023)
This study aims to determine content and conduct exposure assessments of benzene and benzoic acid in functional beverages. A total of 47 functional drink products were purchased from convenience stores in Bangkok, Thailand. Benzene and benzoic acid contents were determined by high-performance liquid chromatography (HPLC) and gas chromatography–mass spectrometry (GC–MS), respectively. Risk characterisations of exposures to benzoic acid were assessed by hazard quotient. Margin of exposure and cancer risk approaches were used for exposure assessment of benzene. The results showed that benzoic acid levels ranged from 74–229 mg L−1 complying with Thai food standards and the Codex Alimentarius. Benzene concentrations varied between 0.60–551 μg L−1, and 14 samples (30%) had concentrations above the limit of 10 μg L−1 recommended by World Health Organization. Regularly high consumption of vitamin C-enriched drinks containing benzoic acid results in high exposure to benzene with attendant cancer risk. To reduce health risks, drinks containing benzoic acid as a preservative should not be fortified with vitamin C.